2004
DOI: 10.1097/01.ico.0000136673.35530.e3
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Cornea Using Scanning-Slit Corneal Topography in Eyes Undergoing Excimer Laser Refractive Surgery

Abstract: Myopic PRK and LASIK induce significant forward shifts of the cornea, which are not true corneal ectasia. Eyes with thinner corneas and higher myopia requiring greater ablation are more predisposed to anterior protrusion of the cornea. Corneal forward shift was progressive up to 6 months after PRK but not progressive after LASIK. Forward shift of the cornea can be one of the factors responsible for myopic regression after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…Moreover, the biomechanical properties of the cornea may affect not only the refractive outcomes after keratorefractive surgery such as laser in situ keratomileusis (LASIK), leading to unpredictability for this surgical technique [1][2][3][4][5], but also the measurement of the intraocular pressure (IOP) especially in eyes undergoing LASIK [6][7][8][9]. Thus, it is of clinical importance to assess the biomechanical properties of the cornea, but the methodology for the in vivo assessment of corneal biomechanics has not long been established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the biomechanical properties of the cornea may affect not only the refractive outcomes after keratorefractive surgery such as laser in situ keratomileusis (LASIK), leading to unpredictability for this surgical technique [1][2][3][4][5], but also the measurement of the intraocular pressure (IOP) especially in eyes undergoing LASIK [6][7][8][9]. Thus, it is of clinical importance to assess the biomechanical properties of the cornea, but the methodology for the in vivo assessment of corneal biomechanics has not long been established.…”
Section: Introductionmentioning
confidence: 99%
“…However, the risk of the development of iatrogenic keratectasia, resulting from the biomechanical weakening of the cornea, has been reported especially after laser in situ keratomileusis (LASIK) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] , suggesting that LASIK, which requires not only surgical tissue subtraction but also flap creation, in some cases may impair the biomechanical strength of the cornea. The biomechanical properties of the cornea may affect not only the refractive outcomes after keratorefractive surgery such as LASIK, leading to the unpredictability of this surgical technique [16][17][18][19][20] , but also the measurement of the intraocular pressure especially in eyes undergoing LASIK [21][22][23][24] . In consideration of the presence of delayed-onset keratectasia [3,4,10,14] , it is possible that the postoperative corneal biomechanics might be compromised with time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reaching stability of refraction after surgery needs more time, and iatrogenic keratoectasia may easily happen in these eyes [13,14,15,16]. Fortunately, in most cases, the biomechanical bowing of the cornea is not a true corneal ectasia [3]. From this point of view, lowering the IOP preoperatively and postoperatively may be an effective way to prevent myopic regression and iatrogenic keratoectasia after LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…Kamiya et al [3] reviewed the time course of the corneal anteroposterior shift after LASIK. It was shown that eyes with thinner corneas and higher degrees of myopia, which require a greater ablation depth, are more predisposed to anterior protrusion of the cornea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation